Severe thunderstorm, Jersey, 25 June 2020. (31st March 2021) - Winter, Matt; Galvin, Jim
Abstract : During the evening of 25 June 2020, thunderstorms developed over northern France before moving northwards towards the Channel Islands. One of these developed into a severe thunderstorm which affected Jersey for a couple of hours giving frequent lightning, strong gusts and torrential downpours leading to localised flash flooding. This article investigates the causes, development and impacts of the storm alongside some of the challenges associated with forecasting severe convection for a small island.